Hyoid Elongation May Be a Rare Cause of Recurrent Ischemic Stroke in Youth-A Case Report and Literature Review - Liu, Gang; Wang, Yuan; Chu, Changbiao; Ren, Yi; Hua, Yang; Ji, Xunming; Song, Haiqing (Frontiers in Neurology, 2021)
The investigation for etiology of stroke in young adults remains a diagnostic challenge. Hyoid bone–related carotid injury is a rare and under-recognized cause of stroke, without established guidelines. We describe a case of recurrent stroke in a young patient presumably attributed to an impingement of the carotid artery by an elongated hyoid bone, and present other cases reported in the literature. Based on the imaging study as well as the lack of other findings, we attributed recurrent neurovascular events to the repetitive mechanical stimulation by the elongated hyoid bone that caused a vessel wall injury with subsequent thrombus and embolus. Given repeated recurrence under antiplatelet treatment, anticoagulation was added. The following 2-year follow-up showed no new neurologic events or any other complaints. Among the young, a broad spectrum of possibilities should be considered and we call attention to this infrequent etiology of stroke.